Water quality analysis of Ulu Bendul Negeri Sembilan Waterfall / Muhamad Akmal Hakim Daud - Daud, Muhamad Akmal Hakim (2014)
Water Quality (WQ) is a tool to determine conditions of water and require knowledge about principles and basic concepts of water and related issues and determined by many physical, chemical and biological factors. Water quality analysis of Ulu Bendul Waterfall, Negeri Sembilan was carried out in five weeks starting from the end of March until April 2014.Six selected stations at different localities and water quality level was selected under this study. Eight physical and biological parameters of the sample were measured are pH, temperature, Dissolved Oxygen ( DO), Biological Oxygen Demand ( BOD), Total Suspended Solid ( TSS), turbidity, salinity and total coliform. The mean value of the measured parameters was compared with Interim National Quality Water Standard (INQWS) and Water Quality Index Department of Environment (DOE) for analysis and categorization. The classes that are indicated by each parameter showed as follow: pH (IIA), temperature (I, IIB, IV AND V), Dissolved Oxygen (IIA and IIB), Biological Oxygen Demand (IIA and IIB), Total Suspended Solid (V), Turbidity (IIA AND IIB), Salinity (IIB, III, IV, V) and total coliform (V).Three parameter had shown significant difference which are Dissolved Oxygen (DO), Total Suspended Solid (TSS) and total coliform bacteria. In conclusion, it present that water quality of Ulu Bendul is suitable for recreational place but Total Suspended Solid (TSS) need to be concern. The values measured are also highly expected to have relation with human activities, environment, weather and other factors.